(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
This thesis explores the role of the English language in social media, analyzing its use and impact on global communication, cultural exchange, and identity formation. Given the pervasive nature of English in digital platforms, this study investigates how English functions as a lingua franca in online environments, the effects of its widespread use on local languages and cultures, and the implications for global communication practices.